Pemanfaatan Eco Enzyme Untuk Mendegradasi Kadar BOD Dan COD Pada Air Limbah Industri Tahu - Stientje, Stientje; Muharram, Fadel; Sahani, Wahyuni (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Tofu liquid waste contains various organic and inorganic substances at high concentrations. This substance makes the Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) increasing quite high. One efficient and environmentally friendly alternative is the use of eco enzyme, which is a natural enzyme produced through fermentation of organic materials. Eco enzyme has the ability to decompose organic substances in liquid waste more effectively, it can also reduce BOD and COD levels, and energy use in the process. The type of research used in this research is quasi-experimental research by determining the ability of eco enzymes to decreasing BOD and COD levels in tofu industrial wastewater by treating three variations of doses 5,10 and 15 on a laboratory scale with two replications (repetitions). Eco enzyme will be added to the sample of tofu industrial wastewater with variation of dose each 5,10 and 15 ml then given a residence time by twenty days. After twenty days the sample of tofu industry wastewater will be taken to check the BOD and COD levels, then will be analyze and interpreted descriptively to determine the BOD and COD levels. The results of the study showed that out of three dose variants, the one that showed the greatest decrease was the 10 ml dose, where the percentage decrease in BOD was 89.8% and for COD was 56.6%, while for the other doses there was also a decrease, but the percentage was not as much as the 10 ml dose. Suggestions for future researchers are to combine other processing methods with the addition of eco enzyme to reduce the time that will be required. Keywords : Eco enzyme, Tofu liquid waste, BOD, COD